Entering work and the British tax and benefit system - Paul Gregg; Paul Johnson; Howard Reed (Institute for Fiscal Studies (IFS), 1999)
The report shows what differentiates the individuals in the survey who entered work over a twelve month period from those who remained out of work over the course of a year. It examines how the distribution of hourly wages earned by new entrants into jobs differs from the distribution of wages for those already in work. This 'entry wage' information is just used to estimate gains to working for people who are currently unemployed or inactive, and to assess to what extent financial incentives affect entry into work. The report also simulates what the effect of the WFTC, the NI reforms, and the 10p tax rate might be on the numbers of men and women entering work and how these reforms might increase employment.
Keywords: 330